Greening the globe: a multi-stage analysis of human capital, innovation-policy interactions, and renewable energy in driving environmental sustainability - Yu Wence; Chuhao Wang; Xue Zhao; Zhang Haiyuan (Frontiers in Environmental Science)
Economic growth must be balanced with ecological sustainability as G20 nations face mounting environmental concerns and sustainability challenges. These countries account for the majority of global economic output and emissions, making them pivotal in efforts to reduce ecological footprints while fostering innovation and economic progress. This study introduces a novel approach by integrating advanced econometric methods such as Cross-Sectional Augmented ARDL (CS-ARDL), Augmented Mean Group (AMG), Common Correlated Effects Mean Group (CCEMG), and Granger causality tests to comprehensively analyze the dynamic relationships between ecological footprint (EFP), environmental policies (EP), renewable energy consumption (REC), capital formation (CF), and innovation (INN) in G20 countries from 1990 to 2023. The key novelty of this study lies in its methodological rigor and ability to address cross-sectional dependence and heterogeneity within the G20 economies. Unlike prior research, this study simultaneously examines linear, nonlinear, and interaction effects, providing a holistic understanding of how economic and environmental factors interact over time. The CS-ARDL results highlight that environmental policies, innovation, and renewable energy consumption drive ecological sustainability, with REC playing the most significant role in reducing EFP over time. The findings on capital formation and economic growth further emphasize that sustainable development hinges on strategic investments in human and physical capital. By leveraging AMG and CCEMG methodologies, this research strengthens the robustness of its findings, ensuring their validity across diverse economic contexts. Granger causality analysis reveals a bidirectional relationship between EFP and innovation and a unidirectional link between REC and EP, underscoring the critical role of renewable energy in shaping environmental policy. This study offers groundbreaking empirical insights into the economic, environmental, and innovation dynamics of G20 nations, advocating for policies that prioritize renewable energy, technological advancements, and sustainable capital investments. Future research should explore sector-specific dynamics and the socio-political dimensions of sustainable development pathways.